ARTEMIA IN WEANING TO BALANCED FOOD CONSUMPTION OF Arapaima gigas - FERNÁNDEZ MÉNDEZ, Christian (2017)
Arapaima gigas is a fish native to the Amazon that has generated great interest for aquaculture due to its characteristics that favor cultivation. However, one of the first difficulties in the fish farming especially of piscivorous habits is the weaning of live food to dry balanced diets. The aim of the present study was to evaluate the use of artemia in the weaning of balanced feed of A. gigas. We used 749 fish (1,61 ± 0,26 g and 6,49 ± 0,32 cm) that were conditioned in glass aquariums with 60 L of water. For the first day they were fed with artemia nauplii only to apparent satiety, the second to the eighth day was nauplii gradually reduced and the balanced food powder (50% PB) was increasing. From the ninth day they were fed only with balanced feed until 27 days. At the end of the experiment, the fish reached an average weight of 9,38 ± 1,57 g; a total length of 10,53 ± 0,54 cm and survival of 94,0 ± 1,1%. A. gigas can wean to balanced food quickly when the co-feeding with artemia nauplii is performed for 6 days.